War from the ground up twenty-first century combat as politics - Simpson, Emile (Crises in world politics, 2013)
Analyzes contemporary armed conflict from the point of view of a British infantry officer with experience on the battlefield; considers the concepts involved and the blurring of military and political activity that has challenged the distinction between war and peace.